PEEK composite resin with enhanced intumescent flame retardancy loaded with Octaphenylsilsesquioxane and nano calcium carbonate and its application in fibers. (August 2022) - Zhou, Xingyu; Yu, Rui; Jiang, Junhui; Dang, Junbo; Luan, Jiashuang; Wang, Guibin; Zhang, Mei
Highlights: A facile and useful method was provided for solving melt flowage and drop of PEEK in the fire, which widens the application of PEEK and could be generalized to other thermoplastic engineering plastics. Novel intumescent flame retardants containing nano-calcium carbonate (nCC) and octaphenylsilsesquioxane (OPS) for effective application in PEEK. This synergistic flame retardant system is also suitable for PEEK fibers, finding an effective flame retardant method for thermoplastic high-performance polymer fabrics. Abstract: This study reported a novel strategy of introducing nano Calcium Carbonate (nCC) and Octaphenylsilsesquioxane (OPS) simultaneously into poly ether ether ketone (PEEK) as the intumescent flame retardants for the first time to address the melt flowage and drop in the fire. Good dispersion of nCC and OPS in the PEEK matrix was observed. The nanocomposites displayed lower thermal decomposition rate and higher residual chars compared with those of pristine PEEK. Cone calorimeter tests showed that the peak heat release rate, smoke production rate and the total smoke production of 5%OPS/5%nCC/PEEK decreased by 47.54%, 55.00% and 30.61%, respectively. Furthermore, the combustion mechanism of PEEK and its nanocomposite was investigated by TG-MS, which showed that nCC and OPS had a synergistic flame retardant effect. Finally, as an application verification, the PEEK nanocomposite fiber was prepared and its flame retardant properties were basically the same as the PEEK nanocomposite material, proving its huge application potential in high-performance flame retardant fabrics. This work is expected to pave the pathway about the novel eco-friendly flame retardancy and open a new avenue to develop PEEK nanocomposites. Graphical: Image, graphical abstract